2015
DOI: 10.6061/clinics/2015(09)05
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a discrepancy between actual and preferred living arrangements on life satisfaction among the elderly in China

Abstract: OBJECTIVES:To explore the effects of a discrepancy between actual and preferred living arrangements on the relationship between living arrangements and life satisfaction among the elderly in China.METHODS:Secondary analysis of the 2005 dataset of the Chinese Longitudinal Healthy Longevity Survey was performed. A binary logistic regression model was used to analyze the relationship between life satisfaction and living arrangements.RESULTS:Among those with concordant actual and preferred living arrangements, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
(19 reference statements)
0
15
0
Order By: Relevance
“… 32 On the contrary, a study in China showed living in a nursing home was associated with increased life satisfaction. 33 Few studies have investigated life satisfaction as an antecedent of nursing home admission. This paper makes a contribution by showing the indirect effect of life satisfaction on intention to live in nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“… 32 On the contrary, a study in China showed living in a nursing home was associated with increased life satisfaction. 33 Few studies have investigated life satisfaction as an antecedent of nursing home admission. This paper makes a contribution by showing the indirect effect of life satisfaction on intention to live in nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that these adolescents may have difficulty regulating their emotion contributing to the development of psychological problems (27). The presence of negative outcomes (such as punitive responses) is associated with agitated-relation emotions (28). In adolescence, the parents serve as an emotional resource; hence, the mother's acceptance of her own emotions seems to be consistently correlated with adolescent adjustment (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has shown [7][8][9][10], living arrangements have long been regarded as the foundation of oldest-old care and are closely connected with the physical and psychological well-being of the oldest-old and social resource allocation. Living in a nursing home is a good option for the Chinese elderly care according to explore the impact of the discrepancy between actual and preferred living arrangements on life satisfaction among the oldest old in China [11].…”
Section: Introductionmentioning
confidence: 99%